New Metrics for Dynamic Analysis of Online Radicalization. Issue 2 (2nd April 2016) - Wadhwa, Pooja; Bhatia, M. P. S.
ABSTRACT: The increasing use of online social networks (OSNs) by extremists for the spread of radicalization have been a great concern for law enforcement agencies across the world. Today, they are being increasingly used by radical groups for spreading ideologies, recruitment, influencing and planning their activities. However, many of such groups remain hidden within the social fabric and can only be discovered by analyzing the related content posted by them. This article addresses the missing line of research by analyzing hidden online Radical networks along three dimensions—element level, group-level, and network level and addresses the gap which the present metrics for social network analysis fail to address as we graduate toward the dynamic network analysis. We propose new metrics to analyze the evolving topic-centric network and present our findings about the understanding of properties of such complex networks in the information network of Twitter with the existing as well the new proposed metrics.